Reduced frequency of perforin-positive CD8+ T cells in menstrual effluent of endometriosis patients - Schmitz, Timo; Hoffmann, Verena; Olliges, Elisabeth; Bobinger, Alina; Popovici, Roxana; Nößner, Elfriede; Meissner, Karin (Journal of reproductive immunology, 2021)
Endometriosis is a widespread disease and commonly reduces the life quality of those affected. Scientific literature indicates different underlying immunological changes. Frequently examined tissues are peripheral blood, endometrial tissue and peritoneal fluid. Yet, knowledge on immunological differences in menstrual effluent (ME) is scarce. In this study, between January 2018 and August 2019, 12 women with endometriosis (rASRM classification: stages I-IV) and 11 healthy controls were included. ME was collected using menstrual cups and venous blood samples (PB) were taken. Mononuclear cells were obtained from ME (MMC) and PB (PBMC) and analyzed using flow cytometry. Concentrations of cell adhesion molecules (ICAM-I and VCAM-I) and cytokines (IL-6, IL-8 and TNF-α) were measured using ELISA. CD8 + T cells obtained from ME were significantly less often perforin-positive in women with endometriosis compared to healthy controls. A comparison between MMC and PBMC revealed that MMC contained significantly less T cells and more B cells. The CD4/CD8 ratio was significantly higher in MMC, and Tregs were significantly less frequently in MMC. In ME, T cells and NK cells expressed significantly more CD69. NK cells obtained from ME were predominantly CD56bright/CD16dim and had a lower frequency of perforin + cells compared to PBMC NK cells. Moreover, ICAM-1 plasma levels were significantly reduced in women with endometriosis compared to healthy controls. In conclusion, CD8 + T cells obtained from the ME were significantly less perforin-positive in endometriosis patients indicating a reduced cytotoxic potential. MMC are distinctively different from PBMC and, thus, seem to be of endometrial origin.
Gesehen am 05.01.2022